Multivalent hyaluronic acid bioconjugates improve sFlt-1 activity in vitro. (July 2016) - Altiok, Eda I.; Santiago-Ortiz, Jorge L.; Svedlund, Felicia L.; Zbinden, Aline; Jha, Amit K.; Bhatnagar, Deepika; Loskill, Peter; Jackson, Wesley M.; Schaffer, David V.; Healy, Kevin E.
Abstract: Anti-VEGF drugs that are used in conjunction with laser ablation to treat patients with diabetic retinopathy suffer from short half-lives in the vitreous of the eye resulting in the need for frequent intravitreal injections. To improve the intravitreal half-life of anti-VEGF drugs, such as the VEGF decoy receptor sFlt-1, we developed multivalent bioconjugates of sFlt-1 grafted to linear hyaluronic acid (HyA) chains termed mvsFlt. Using size exclusion chromatography with multiangle light scattering (SEC-MALS), SDS-PAGE, and dynamic light scattering (DLS), we characterized the mvsFlt with a focus on the molecular weight contribution of protein and HyA components to the overall bioconjugate size. We found that mvsFlt activity was independent of HyA conjugation using a sandwich ELISA and in vitro angiogenesis assays including cell survival, migration and tube formation. Using an in vitro model of the vitreous with crosslinked HyA gels, we demonstrated that larger mvsFlt bioconjugates showed slowed release and mobility in these hydrogels compared to low molecular weight mvsFlt and unconjugated sFlt-1. Finally, we used an enzyme specific to sFlt-1 to show that conjugation to HyA shields sFlt-1 from protein degradation. Taken together, our findings suggest that mvsFlt bioconjugates retain VEGF binding affinity, shield sFlt-1 from enzymatic degradation, and their movement in hydrogel networks ( in vitro model of the vitreous) is controlled by both bioconjugate size and hydrogel network mesh size. These results suggest that a strategy of multivalent conjugation could substantially improve drug residence time in the eye and potentially improve therapeutics for the treatment of diabetic retinopathy.